The Fourth-Order Single-Switch Improved Super-Boost Converter with Reduced Input Current Ripple - Enrique Garza-Arias; Rosas-caro, Julio; Jesus E. Valdez-Resendiz; Mayo Maldonado, Jonathan; Gerardo Escobar-Valderrama; Daniel Guillen (My University, 2021)
This paper introduces a new single switch DC-DC fourth-order boost converter. The proposed converter is the improved version of an existing converter known as the super-boost converter. The improved super-boost ISP converter achieves a smaller input current ripple than the super-boost converter when the same parameters in passive components are used. Conversely, smaller components can be used to achieve the same input current ripple, which leads to a compact and cheaper design. A comparative evaluation showed a reduction of 37.3% of stored energy in inductors to comply with a required input current ripple in comparison with the super-boost converter for a particular design. Experimental results are provided to corroborate this benefit of the ISB proposed topology.